Analysis of Information Security Resource Requirements in Local Governments - Toto, Suharto; Aisyah, Nuraeni; Awan, Setiawan (INTI International University, 2022)
Information Security Resources Needs Analysis and Management in Local Government is compiling the information security resource requirements by the Regional Government so the implementation of information security can guarantee the confidentiality, integrity, and availability of information. The lack of related research causes innovation and the fulfillment of information resource needs not to develop. Therefore, this study aims to carry out the local government's information security resources needs with a portrait adapted to existing conditions. In this study, the methodology used is Input-Process-Output and the objects of information security resources are asset security management, human resource management, and knowledge management which carry out city government affairs and must comply with applicable regulations and policies.